DRAMA IN SCHOOL. AN EDUCATIONAL INITIATIVE FOR THE FUTURE - Sylvia ROTTER; Ciprian NIŢIŞOR (National Centre for Policy and Evaluation in Education, 2017)
The aim of this paper is to highlight experiences and benefits of drama in education that have been developed through the project "The National Educational Initiative - Drama in education". The project was carried out in 2014 in Romanian secondary schools by the Vienna Theatre for Children Association. The initiative addressed to children, teens and teachers alike. The starting point of the project lies in the research and methodology that were developed within the "School for Life" initiative of the Vienna Theatre for Children in 2008. The focal point consists in exploring the impact of play in education and learning. The two projects that are mentioned in the paper identified and evaluated the skills of the children and youth who got involved in the drama activities. The results showed cognitive, emotional and interpersonal progress in acquisition.